Thermally conductive sheet and method for manufacturing the same
The thermally conductive sheet with a specified surface roughness and regular shape effectively addresses air entrapment and thermal resistance variations, ensuring reliable heat dissipation and adhesion without physical surface processing.
Patent Information
- Application Number
- JP2021028001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-24
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-02-24
AI Technical Summary
Conventional thermally conductive sheets face challenges in preventing air entrapment during mounting and maintaining consistent thermal resistance due to varying loads, especially with larger sizes and complex adherends like IC chips.
A thermally conductive sheet with a surface arithmetic mean roughness (Sa) of 5.0 μm or more and a thickness of 0.3 mm, achieving a thermal resistance of 5kgf/cm at 0.3mm, with a thermal resistance difference of less than 0.08°C·cm²/W, manufactured by pressing a precursor with a regular shape transferred from a cushion or film.
The solution effectively prevents air entrapment and reduces thermal resistance variations under different loads, ensuring uniform heat dissipation and improved adhesion without physical surface processing, thus enhancing the thermal conductivity and reliability of the sheet.
Smart Images

Figure 0007602931000002 
Figure 0007602931000003 
Figure 0007602931000004
Abstract
Description
[Technical field]
[0001] The present technology relates to a thermally conductive sheet and a method for manufacturing the thermally conductive sheet. [Background technology]
[0002] Conventionally, semiconductor elements mounted in various electrical devices such as personal computers and other devices generate heat when operated. If the generated heat accumulates, it may have an adverse effect on the operation of the semiconductor elements and on peripheral devices, so various cooling methods have been used.
[0003] Known methods for cooling a device having a semiconductor element include a method of attaching a fan to the device to cool the air inside the device housing, a method of attaching a heat sink such as a heat dissipation fin or a heat sink to the semiconductor element, a method of immersing in a fluorine-based inert liquid, etc. When cooling by attaching a heat sink to a semiconductor element, a thermally conductive sheet is provided between the semiconductor element and the heat sink in order to efficiently dissipate heat from the semiconductor element.
[0004] As an example of a thermally conductive sheet, one in which a filler (for example, a thermally conductive filler such as carbon fiber) is dispersed in a binder resin is widely used (see, for example, Patent Document 1).
[0005] Incidentally, electronic components such as the central processing unit (CPU) of a personal computer tend to dissipate more heat every year as their speed and performance improve. However, with the advancement of micro-silicon circuit technology, the chip size of processors and the like has become smaller than before, and the heat flow rate per unit area has increased. In order to avoid problems caused by temperature rise in such electronic components, there is a demand for more efficient heat dissipation and cooling of electronic components.
[0006] In order to improve the heat dissipation characteristics of a thermally conductive sheet, for example, it is necessary to reduce the thermal resistance, which is an index showing how difficult it is to transfer heat. In order to reduce the thermal resistance of a thermally conductive sheet, for example, it is effective to improve the adhesion of the thermally conductive sheet to a heat generating body (e.g., an electronic component) or a heat dissipating body (e.g., a heat sink).
[0007] For example, in the techniques described in Patent Documents 2 and 3, the thermally conductive sheet is pressed to increase the smoothness of the surface of the thermally conductive sheet, improving contact and reducing thermal resistance.
[0008] In recent years, the size of the thermally conductive sheet used has increased as the size of the adherend (e.g. IC chip) has increased. For example, when mounting a large, thin thermally conductive sheet with tack all over the surface on an IC chip, if the surface of the thermally conductive sheet is smooth, air (air bubbles) are likely to be trapped between the thermally conductive sheet and the IC chip, and if pressure is applied in this state, there is a risk of the thermally conductive sheet breaking inside. This causes the in-plane thickness of the thermally conductive sheet to become uneven, increasing the contact thermal resistance, and it may be difficult to reduce the thermal resistance of the thermally conductive sheet. In addition, thermally conductive sheets with smooth surfaces tend to have a large difference in thermal resistance due to load, and if there is a bias in the magnitude of the load applied by the adherend, there is a risk that the thermal resistance cannot be sufficiently reduced.
[0009] Similarly, when a large thermally conductive sheet is picked up by an automated machine and mounted on an IC chip, if the surface of the thermally conductive sheet is smooth, the thermally conductive sheet will likely be mounted from multiple edges or parallel to the IC chip, which will tend to trap air in the center between the thermally conductive sheet and the IC chip.
[0010] As described above, in the past, efforts were made to improve contact with heat generating bodies and heat dissipating bodies and reduce thermal resistance by making the surface (adhesive surface) of the thermal conductive sheet smoother. However, when the surface of the thermal conductive sheet is made smoother, air tends to get mixed in when the thermal conductive sheet is mounted, making it difficult to reduce the difference in thermal resistance due to load. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2012-23335 A [Patent Document 2] Patent No. 6178389 [Patent Document 3] Patent No. 5752299 Summary of the Invention [Problem to be solved by the invention]
[0012] The present technology has been proposed in light of the above-mentioned conventional situation, and provides a thermally conductive sheet that is less likely to trap air during mounting and can reduce differences in thermal resistance due to load. [Means for solving the problem]
[0013] The thermal conductive sheet according to the present technology has an arithmetic mean roughness (Sa) of the surface of 5.0 μm or more and a thermal conductivity of 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 / W.
[0014] The method for producing a thermally conductive sheet according to the present technology includes the steps of: step A of preparing a thermally conductive composition containing a binder resin and a fibrous filler; step B of forming a molded body block from the thermally conductive composition; step C of slicing the molded body block into sheets to obtain a thermally conductive sheet precursor; and step D of pressing the thermally conductive sheet precursor to obtain a thermally conductive sheet, the thermally conductive sheet having an arithmetic mean roughness (Sa) of a surface of 5.0 μm or more and a surface roughness of 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 / W. Effect of the Invention
[0015] According to the present technology, it is possible to provide a thermally conductive sheet that is less likely to trap air during mounting and can reduce the difference in thermal resistance due to load. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a thermally conductive sheet. [Diagram 2] FIG. 2 is a cross-sectional view illustrating an example of step D in which the thermally conductive sheet precursor is pressed to obtain the thermally conductive sheet. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. [Figure 4] FIG. 4 is a cross-sectional view illustrating a method of pressing a pressed thermally conductive sheet precursor without attaching a film or cushion having a regular shape to the surface in Comparative Example 2. [Diagram 5] FIG. 5 is a perspective view illustrating an example of a method for measuring the height of the thermally conductive sheet from the copper plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] <Thermal Conduction Sheet> The thermal conductive sheet according to the present technology has an arithmetic mean roughness (Sa) of the surface of 5.0 μm or more and a thermal conductivity of 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 With such a thermally conductive sheet, air is less likely to be trapped during mounting, the air can be easily released, and the difference in thermal resistance due to load can be reduced.
[0018] The thermal conductive sheet may have a surface arithmetic mean roughness (Sa) of 5.000 μm or more, 5.100 μm or more, 5.200 μm or more, 5.300 μm or more, 5.400 μm or more, 5.500 μm or more, 5.600 μm or more, 5.700 μm or more, 5.800 μm or more, or 5.900 μm or more. The upper limit of the arithmetic mean roughness (Sa) of the surface of the thermal conductive sheet is not particularly limited, but from the viewpoint of more effectively reducing the thermal resistance difference due to the load, it may be, for example, 6.500 μm or less, 6.400 μm or less, 6.300 μm or less, 6.200 μm or less, 6.100 μm or less, or 6.000 μm or less. The arithmetic mean roughness (Sa) of the surface of the thermally conductive sheet may be in the range of 5.400 to 5.950 μm. The arithmetic mean roughness (Sa) of the surface of the thermally conductive sheet can be measured by the method in the examples described later.
[0019] The thermal conductive sheet 1 has a thermal conductivity of 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The smaller the difference in thermal resistance between the 2 / W or less, and 0.08°C cm 2 / W or less, and 0.07°C cm 2 / W or less, and 0.06°C cm 2 / W or less, and 0.05°C cm 2 The thermal resistance of the thermal conductive sheet 1 can be measured by the method described in the Examples below. As a thermal resistance difference due to a load, a low load (1 kgf / cm 2 ) and when a high load (5kgf / cm 2 The reason why the difference in thermal resistance when the thermal conductive sheet 1 is subjected to the above-mentioned temperature change is specified is to make it easier to compare the contact thermal resistance of the thermal conductive sheet 1.
[0020] The thermal conductive sheet 1 has a thermal conductivity of 1 kgf / cm at a thickness of 0.3 mm. 2and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 As long as the difference in thermal resistance between the thermal resistance of the thermal conductive sheet 1 and the thermal resistance of the thermal conductive sheet 2 satisfies the above-mentioned range, the magnitude of the thermal resistance when each load is applied is not particularly limited. 2 Thermal resistance of 0.25℃ cm 2 / W or less, and 0.23°C cm 2 / W or less, and 0.21°C cm 2 The thermal conductive sheet 1 may have a thermal conductivity of 5 kgf / cm at a thickness of 0.3 mm. 2 The thermal resistance of 0.20°C cm 2 / W or less, and 0.18°C cm 2 / W or less, and 0.15°C cm 2 / W or less.
[0021] The thermal conductive sheet 1 preferably has a regular shape on the surface. By having the thermal conductive sheet 1 have a regular shape on the surface, the arithmetic mean roughness (Sa) of the surface of the thermal conductive sheet 1 can be made 5.000 μm or more, and the thermal resistance difference due to the load of the thermal conductive sheet 1 can be more effectively reduced. The regular shape of the thermal conductive sheet 1 is, for example, regular unevenness, and examples of the pattern (shape) of the concave or convex parts in a plan view include a geometric pattern such as a polygonal shape having sides that are not perpendicular to each other, a pattern of multiple circles or ellipses, or a pattern in which such geometric patterns are mixed with circles or ellipses. In addition, the regular shape may be a line-shaped or wavy pattern of the concave or convex parts in a plan view.
[0022] 1 is a cross-sectional view showing an example of a thermally conductive sheet. The thermally conductive sheet 1 includes a binder resin 2 and a fibrous filler 3, and the fibrous filler 3 is oriented in a thickness direction B in a cross-sectional view. For example, in the thermally conductive sheet 1, the major axis of the fibrous filler 3 is oriented in the thickness direction of the thermally conductive sheet 1. The thermally conductive sheet 1 may further include a thermally conductive material 4 other than the fibrous filler 3.
[0023] The thermally conductive sheet 1 preferably has a Shore type OO hardness of more than 30, and may be in the range of 35 to 80, 40 to 75, 45 to 70, or 50 to 70. When the hardness of the thermally conductive sheet 1 is in such a range, for example, when a regular shape is transferred to the surface of the thermally conductive sheet 1 as described later, the formed regular shape (unevenness) can be made less likely to disappear. The hardness of the thermally conductive sheet 1 can be measured by the method described in the Examples below.
[0024] The thickness of the thermally conductive sheet 1 is not particularly limited and can be appropriately selected depending on the purpose. For example, the thickness of the thermally conductive sheet 1 can be 0.05 mm or more, and can also be 0.1 mm or more. The upper limit of the thickness of the thermally conductive sheet 1 can be 5 mm or less, and may be 4 mm or less, or may be 3 mm or less. From the viewpoint of handling, the thermally conductive sheet 1 preferably has a thickness of 0.1 to 4 mm. The thickness of the thermally conductive sheet 1 can be determined, for example, by measuring the thickness of the thermally conductive sheet 1 at any five points and taking the arithmetic average value.
[0025] Specific examples of the components of the thermally conductive sheet 1 will now be described.
[0026] <Binder resin> The binder resin 2 is for holding the fibrous filler 3 and other thermally conductive materials 4 within the thermally conductive sheet 1. The binder resin 2 is selected according to the properties required for the thermally conductive sheet 1, such as mechanical strength, heat resistance, and electrical properties. The binder resin 2 can be selected from thermoplastic resins, thermoplastic elastomers, and thermosetting resins.
[0027] Examples of thermoplastic resins include polyethylene, polypropylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl acetal, fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polystyrene, polyacrylonitrile, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymer (ABS) resins, polyphenylene-ether copolymers (PPE) resins, modified PPE resins, aliphatic polyamides, aromatic polyamides, polyimides, polyamideimides, polymethacrylic acid, polymethacrylic acid esters such as polymethacrylic acid methyl ester, polyacrylic acids, polycarbonates, polyphenylene sulfide, polysulfones, polyethersulfones, polyethernitriles, polyetherketones, polyketones, liquid crystal polymers, silicone resins, and ionomers.
[0028] Examples of the thermoplastic elastomer include a styrene-butadiene block copolymer or a hydrogenated product thereof, a styrene-isoprene block copolymer or a hydrogenated product thereof, a styrene-based thermoplastic elastomer, an olefin-based thermoplastic elastomer, a vinyl chloride-based thermoplastic elastomer, a polyester-based thermoplastic elastomer, a polyurethane-based thermoplastic elastomer, and a polyamide-based thermoplastic elastomer.
[0029] Examples of the thermosetting resin include crosslinked rubber, epoxy resin, phenol resin, polyimide resin, unsaturated polyester resin, diallyl phthalate resin, etc. Specific examples of the crosslinked rubber include natural rubber, acrylic rubber, butadiene rubber, isoprene rubber, styrene-butadiene copolymer rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene copolymer rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butyl rubber, halogenated butyl rubber, fluororubber, urethane rubber, and silicone rubber.
[0030] As the binder resin 2, for example, a silicone resin is preferable in consideration of the adhesion between the heat generating surface of the electronic component and the heat sink surface. As the silicone resin, for example, a two-liquid addition reaction type silicone resin can be used, which is composed of a main component containing a silicone having an alkenyl group, a curing catalyst, and a curing agent having a hydrosilyl group (Si-H group). As the silicone having an alkenyl group, for example, a polyorganosiloxane having a vinyl group can be used. The curing catalyst is a catalyst for promoting the addition reaction between the alkenyl group in the silicone having an alkenyl group and the hydrosilyl group in the curing agent having a hydrosilyl group. As the curing catalyst, a catalyst well known as a catalyst used for a hydrosilylation reaction can be mentioned, for example, a platinum group-based curing catalyst, for example, a platinum group metal such as platinum, rhodium, or palladium, or platinum chloride can be used. As the curing agent having a hydrosilyl group, for example, a polyorganosiloxane having a hydrosilyl group can be used. The binder resin 2 may be used alone or in combination of two or more types.
[0031] The content of the binder resin 2 in the thermal conductive sheet 1 is not particularly limited and can be appropriately selected depending on the purpose. For example, the content of the binder resin 2 in the thermal conductive sheet 1 can be 20 volume % or more, may be 23 volume % or more, may be 25 volume % or more, or may be 28 volume % or more, from the viewpoint of the flexibility of the thermal conductive sheet 1. Furthermore, the content of the binder resin 2 in the thermal conductive sheet 1 is preferably less than 42 volume %, and may be 40 volume % or less, 36 volume % or less, 34 volume % or less, 32 volume % or less, or 30 volume % or less, from the viewpoint of the thermal conductivity of the thermal conductive sheet 1 and the arithmetic mean roughness (Sa) of the sheet surface.
[0032] <Fibrous filler> The thermally conductive sheet 1 preferably contains a fibrous filler 3. The fibrous filler 3 includes those having a long axis and a short axis, the lengths of the long axis and the short axis being different, and having an aspect ratio (average long axis length / average short axis length) exceeding 1. The fibrous filler 3 may be used alone or in combination of two or more types. The fibrous filler 3 can be appropriately selected depending on the purpose, and for example, metal fiber, carbon fiber, etc. can be used, with carbon fiber being preferred.
[0033] Examples of the carbon fiber that can be used include pitch-based carbon fiber, PAN-based carbon fiber, carbon fiber obtained by graphitizing PBO fiber, and carbon fiber synthesized by arc discharge, laser evaporation, CVD (chemical vapor deposition), CCVD (catalytic chemical vapor deposition), etc. Among these, pitch-based carbon fiber is preferred from the viewpoint of thermal conductivity.
[0034] The average fiber length (average major axis length) of the fibrous filler 3 can be, for example, 50 to 250 μm, and may be 75 to 220 μm. The average fiber diameter (average minor axis length) of the fibrous filler 3 can be appropriately selected depending on the purpose, and may be, for example, 4 to 20 μm, and may be 5 to 14 μm. The aspect ratio of the fibrous filler 3 can be appropriately selected depending on the purpose, and may be, for example, 8 or more, and may be 9 to 30, from the viewpoint of thermal conductivity. The average major axis length and average minor axis length of the fibrous filler 3 can be measured, for example, by a microscope or a scanning electron microscope (SEM).
[0035] The surface of the carbon fiber may be coated with an insulating coating depending on the purpose. In this way, an insulating coated carbon fiber can be used as the carbon fiber. The insulating coated carbon fiber has a carbon fiber and an insulating coating on at least a part of the surface of the carbon fiber, and may contain other components as necessary.
[0036] The insulating film is made of a material having electrical insulation properties, and is formed of, for example, silicon oxide or a cured product of a polymerizable material. The polymerizable material is, for example, a radically polymerizable material, and examples thereof include a polymerizable organic compound and a polymerizable resin. The radically polymerizable material can be appropriately selected according to the purpose as long as it is a material that undergoes radical polymerization using energy, and examples thereof include a compound having a radically polymerizable double bond. Examples of the radically polymerizable double bond include a vinyl group, an acryloyl group, and a methacryloyl group. The number of radically polymerizable double bonds in the compound having a radically polymerizable double bond is preferably two or more from the viewpoint of strength including heat resistance and solvent resistance. Examples of the compound having two or more radically polymerizable double bonds include divinylbenzene (DVB) and a compound having two or more (meth)acryloyl groups. The radically polymerizable material may be used alone or in combination of two or more. The molecular weight of the radically polymerizable material can be appropriately selected depending on the purpose and can be, for example, in the range of 50 to 500. When the insulating coating is formed of a cured product of a polymerizable material, the content of structural units derived from the polymerizable material in the insulating coating can be, for example, 50 mass % or more, or can also be 90 mass % or more.
[0037] The average thickness of the insulating coating can be appropriately selected depending on the purpose, and from the viewpoint of realizing high insulation, it can be 50 nm or more, may be 100 nm or more, or may be 200 nm or more. The upper limit of the average thickness of the insulating coating can be, for example, 1000 nm or less, or may be 500 nm or less. The average thickness of the insulating coating can be determined, for example, by observation with a transmission electron microscope (TEM).
[0038] Methods for coating carbon fibers with an insulating film include, for example, the sol-gel method, the liquid phase deposition method, the polysiloxane method, and the method of forming an insulating film made of a cured polymerizable material on at least a part of the surface of the carbon fibers described in JP 2018-98515 A.
[0039] The content of the fibrous filler 3 in the thermal conductive sheet 1 can be, for example, 5 volume % or more, 10 volume % or more, 14 volume % or more, 20 volume % or more, 22 volume % or more, or 24 volume % or more, from the viewpoint of the thermal conductivity of the thermal conductive sheet 1. The content of the fibrous filler 3 in the thermal conductive sheet 1 can be, for example, 30 volume % or less, 28 volume % or less, 26 volume % or less, or 24 volume % or less, from the viewpoint of the moldability of the thermal conductive sheet 1. The content of the fibrous filler 3 in the thermal conductive sheet 1 can be, for example, 5 to 50 volume %, and preferably 14 to 25 volume %. When two or more types of fibrous fillers 3 are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned content.
[0040] <Other heat conductive materials> The other heat conductive material 4 is a heat conductive material other than the above-mentioned fibrous filler 3, and examples thereof include inorganic fillers. Examples of the shape of the other heat conductive material 4 include spherical, crushed, oval-spherical, chunky, granular, flat, and needle-like shapes. From the viewpoint of packing, the shape of the other heat conductive material 4 is preferably spherical, oval-spherical, or the like. The other heat conductive material 4 may be used alone or in combination of two or more kinds.
[0041] Examples of materials for the other thermally conductive material 4 include inorganic fillers, such as aluminum oxide (alumina, sapphire), aluminum nitride, aluminum hydroxide, aluminum, zinc oxide, etc. In particular, from the viewpoints of improving the thermal conductivity of the thermally conductive sheet 1 and reducing the difference in thermal resistance due to the load on the thermally conductive sheet 1, it is preferable to use at least one of alumina and aluminum nitride, and it is more preferable to use alumina and aluminum nitride in combination.
[0042] The average particle size (D50) of the alumina particles can be, for example, 0.1 to 10 μm, may be 0.1 to 8 μm, may be 0.1 to 7 μm, or may be 0.1 to 5 μm. The average particle size (D50) of the aluminum nitride particles can be, for example, 0.1 to 10 μm, may be 0.1 to 8 μm, may be 0.1 to 7 μm, or may be 0.1 to 2 μm. The average particle size of the other heat conductive material 4 refers to the particle size at which the cumulative value of the cumulative curve of the particle size values from the small particle size side of the particle size distribution is 50% when the entire particle size distribution of the other heat conductive material 4 is taken as 100%. The particle size distribution (particle size distribution) is determined by volume standard. For example, a method using a laser diffraction type particle size distribution measuring device can be used to measure the particle size distribution.
[0043] The other thermally conductive material 4 may be surface-treated. For example, the surface treatment may involve treating the other thermally conductive material 4 with a coupling agent such as an alkoxysilane compound. The amount of the coupling agent used may be in the range of 0.1 to 1.5% by volume with respect to the total amount of the other thermally conductive material 4.
[0044] An alkoxysilane compound is a compound having a structure in which, of the four bonds that a silicon atom (Si) has, one to three are bonded to an alkoxy group, and the remaining bonds are bonded to an organic substituent. Examples of the alkoxy group that an alkoxysilane compound has include a methoxy group, an ethoxy group, and a butoxy group. Specific examples of the alkoxysilane compound include a trimethoxysilane compound and a triethoxysilane compound.
[0045] The content of the other heat conductive material 4 in the heat conductive sheet 1 is not particularly limited and can be appropriately selected depending on the purpose. When the heat conductive sheet 1 contains the other heat conductive material 4, the content of the heat conductive material 4 can be more than 21 volume %, may be 36 volume % or more, may be 40 volume % or more, or may be 42 volume % or more from the viewpoint of the thermal conductivity of the heat conductive sheet 1 and reducing the thermal resistance difference due to load. In addition, the content of the other heat conductive material 4 in the heat conductive sheet 1 can be 50 volume % or less, may be 48 volume % or less, or may be 46 volume % or less from the viewpoint of the arithmetic mean roughness (Sa) of the surface of the heat conductive sheet 1. When two or more kinds of the other heat conductive materials 4 are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned content.
[0046] When the thermal conductive sheet 1 includes the fibrous filler 3 and the other thermal conductive material 4, the total content of the fibrous filler 3 and the other thermal conductive material 4 in the thermal conductive sheet 1 can be 57 volume % or more, or may be 60 volume % or more, or may be 63 volume % or more, or may be 65 volume % or more, or may be 68 volume % or more, from the viewpoint of the thermal conductivity of the thermal conductive sheet 1, the arithmetic mean roughness (Sa) of the surface of the thermal conductive sheet 1 being 5.0 μm or more, and reducing the thermal resistance difference. Moreover, the total content of the fibrous filler 3 and the other thermal conductive material 4 in the thermal conductive sheet 1 can be 75 volume % or less, or may be 70 volume % or less, from the viewpoint of the moldability of the thermal conductive sheet 1.
[0047] The thermal conductive sheet 1 may further contain other components in addition to the above-mentioned components, as long as the effect of the present technology is not impaired. Examples of the other components include dispersants, curing accelerators, retarders, tackifiers, plasticizers, flame retardants, antioxidants, stabilizers, and colorants.
[0048] <Method of manufacturing thermal conductive sheet> The method for producing a thermally conductive sheet according to the present technology includes step A of preparing a thermally conductive composition containing a binder resin 2 and a fibrous filler 3, step B of forming a molded block from the thermally conductive composition, step C of slicing the molded block into sheets to obtain a thermally conductive sheet precursor, and step D of pressing the thermally conductive sheet precursor to obtain the above-mentioned thermally conductive sheet 1.
[0049] [Process A] In step A, a thermally conductive composition is prepared, which includes a binder resin 2 and a fibrous filler 3. The thermally conductive composition may include other thermally conductive materials 4 as described above. The thermally conductive composition may be uniformly mixed with various additives and volatile solvents by known methods.
[0050] [Process B] In step B, a molded block is formed from the thermal conductive composition. Examples of methods for forming the molded block include extrusion molding and die molding. The extrusion molding and die molding are not particularly limited, and can be appropriately selected from various known extrusion molding and die molding methods according to the viscosity of the thermal conductive composition and the properties required for the thermal conductive sheet 1. For example, when the thermal conductive composition is extruded from a die in the extrusion molding method, or when the thermal conductive composition is pressed into a die in the die molding method, the binder resin 2 flows, and the long axis of the fibrous filler 3 is oriented along the flow direction.
[0051] The size and shape of the molded block can be determined according to the size of the desired thermally conductive sheet. For example, a rectangular parallelepiped with a cross-sectional vertical dimension of 0.5 to 15 cm and a horizontal dimension of 0.5 to 15 cm can be used. The length of the rectangular parallelepiped can be determined as necessary. In the extrusion molding method, it is easy to form a columnar molded block made of a cured product of the thermally conductive composition, in which the major axis of the fibrous filler 3 is oriented in the extrusion direction.
[0052] The obtained molded block is preferably thermally cured. The curing temperature in the thermal curing can be appropriately selected depending on the purpose, and for example, when the binder resin 2 is a silicone resin, it can be in the range of 60° C. to 120° C. The curing time in the thermal curing can be in the range of 30 minutes to 10 hours, for example.
[0053] [Process C] In step C, the molded body block is sliced into sheets to obtain a thermally conductive sheet precursor in which the long axis of the fibrous filler 3 is oriented in the thickness direction B. The fibrous filler 3 is exposed on the surface (sliced surface) of the thermally conductive sheet precursor obtained by slicing. There is no particular limitation on the slicing method, and it can be appropriately selected from known slicing devices depending on the size and mechanical strength of the molded body block. Examples of slicing devices include ultrasonic cutters and planes. When the molding method is extrusion molding, the slicing direction of the molded body block is preferably 60 to 120 degrees relative to the extrusion direction, more preferably 70 to 100 degrees, and even more preferably 90 degrees (perpendicular) because some molded body blocks have their long axis oriented in the extrusion direction.
[0054] [Process D] In step D, the thermally conductive sheet precursor is pressed to obtain the thermally conductive sheet 1. In step D, by pressing the thermally conductive sheet precursor, the binder resin 2 constituting the thermally conductive sheet precursor 7 seeps out onto the surface of the thermally conductive sheet 1 (the thermally conductive sheet precursor after pressing), and the thermally conductive sheet 1 becomes tacky. The binder resin 2 seeping out onto the surface of the thermally conductive sheet 1 may be in an uncured state, or may be in a state in which curing has progressed by about several percent. The thermally conductive sheet 1 obtained in step D has a smoother surface, which can further improve the adhesion between the thermally conductive sheet 1 and other members.
[0055] In step D, for example, the sliced surface (surface) of the thermal conductive sheet precursor is pressed to transfer a regular shape to the surface of the thermal conductive sheet precursor. In one embodiment of step D, a film or cushion having a regular shape on its surface is attached to the surface of the thermal conductive sheet precursor and pressed, thereby transferring the shape of the film or cushion surface to the surface of the thermal conductive sheet precursor. In addition, in step D, a laminate (a laminate of a film having a smooth surface, the pressed thermal conductive sheet precursor, and a film having a smooth surface) obtained by sandwiching and pressing the sliced surface of the thermal conductive sheet precursor between films having a smooth surface may be further pressed with a film or cushion having a regular shape on its surface, thereby transferring the shape of the film or cushion surface having a regular shape to the surface of the thermal conductive sheet precursor.
[0056] FIG. 2 is a cross-sectional view for explaining an example of step D in the manufacturing method of a thermally conductive sheet, in which a thermally conductive sheet precursor is pressed to obtain a thermally conductive sheet. The arrow in FIG. 2 indicates the pressing direction. In step D, as shown in FIG. 2, the thermally conductive sheet precursor 7 is sandwiched between release films 6A and 6B, and a cushion 8 (hereinafter, simply referred to as "cushion 8") having a regular shape on the surface is placed on the outside of the release films 6A and 6B. That is, a laminate 10 having the cushion 8A, release film 6A, thermally conductive sheet precursor 7, release film 6B, and cushion 8B in this order may be pressed. By pressing such a laminate 10, the shape of the surface of the cushion 8 can be transferred to the surface of the thermally conductive sheet precursor 7. In addition, by using the cushion 8 having a regular shape on the surface, the surface of the thermally conductive sheet precursor 7 can be pressed uniformly, and the thermal resistance of the thermally conductive sheet 1 can be effectively reduced. Furthermore, by sandwiching the thermally conductive sheet precursor 7 between release films 6A and 6B when pressing the thermally conductive sheet precursor 7, it is possible to prevent the thermally conductive sheet precursor 7 from adhering to the pressing device when pressing the thermally conductive sheet precursor 7.
[0057] In step D, as shown in FIG. 2, the thermally conductive sheet precursor 7 is sandwiched between release films 6A and 6B, and a film 9 having a regular shape on its surface (hereinafter, simply referred to as "film 9") is placed on the outside of the release films 6A and 6B. That is, a laminate 11 having the film 9A, release film 6A, thermally conductive sheet precursor 7, release film 6B, and film 9B in this order may be pressed. By pressing such a laminate 11, the shape of the surface of the film 9 can be transferred to the surface of the thermally conductive sheet precursor 7. In addition, by using the film 9 having a regular shape on its surface, the surface of the thermally conductive sheet precursor 7 can be pressed uniformly, and the thermal resistance of the thermally conductive sheet 1 can be effectively reduced.
[0058] Although not shown, in step D, a cushion 8 having a regular shape on its surface and a film 9 having a regular shape on its surface may be used in combination. For example, in step D, the thermally conductive sheet precursor 7 may be sandwiched between release films 6A and 6B, and further, the cushion 8 having a regular shape is placed on the outer surface of the release film 6A, and the film 9 having a regular shape is placed on the outer surface of the release film 6B, that is, a laminate having the cushion 8, release film 6A, thermally conductive sheet precursor 7, release film 6B, and film 9 in this order may be pressed.
[0059] Examples of the release film 6 include PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyolefin, polymethylpentene, glassine paper, and the like. The thickness of the release film 6 is not particularly limited and can be appropriately selected depending on the purpose, and can be, for example, 5 to 200 μm. Furthermore, the thinner the release film 6, the better the conformability (adhesion) to the thermal conductive sheet 1, and the more effectively the tackiness of the thermal conductive sheet 1 can be exhibited. For example, from the viewpoint of more effectively exhibiting the tackiness of the thermal conductive sheet 1, the release film 6 is preferably a thin PET film. The release film 6A and the release film 6B may be made of the same material or different materials. The release film 6A and the release film 6B may be made of the same thickness or different thicknesses.
[0060] The cushion 8 may have a pattern in a plan view with a regular shape as described above. The material of the cushion 8 may be, for example, rubber. A specific example of the cushion 8 is a product named YOM-F01 FDRR manufactured by Yamauchi Corporation. The thickness of the cushion 8 is not particularly limited and may be appropriately selected depending on the purpose. The cushions 8A and 8B may have the same or different regular shapes on the surface. The cushions 8A and 8B may be made of the same or different materials. The cushions 8A and 8B may have the same or different thicknesses.
[0061] The film 9 may have a pattern in a plan view with a regular shape as described above. For example, an embossed film having a regular uneven surface may be used. The material of the film 9 is not particularly limited, and for example, PET may be used. Specific examples of the film 9 include products under the names "ALEF", "EF", "NEF", and "Ko-Diamond" (all manufactured by Ishijima Chemical Industry Co., Ltd.). The film 9A and the film 9B may be made of the same material or different materials. The film 9A and the film 9B may have the same regular surface shape or different shapes. The thickness of the film 9 is not particularly limited, and may be appropriately selected according to the purpose, and may be in the range of, for example, 0.004 to 0.3 mm. The film 9A and the film 9B may have the same thickness or different thicknesses.
[0062] A pair of press devices 5 consisting of a flat plate and a press head with a flat surface can be used to press the thermally conductive sheet precursor 7. The thermally conductive sheet precursor 7 may also be pressed with a pinch roll. The pressure during pressing may be, for example, in the range of 0.1 to 100 MPa, may be in the range of 0.1 to 1 MPa, or may be in the range of 0.1 to 0.5 MPa. The pressing temperature may be, for example, in the range of 0 to 180°C, may be in the range of room temperature to 100°C, or may be in the range of 30 to 100°C. In this specification, "room temperature" refers to the range of 15 to 25°C as specified in JIS K 0050:2019 (General Rules for Chemical Analysis Methods). In order to further enhance the effect of pressing and shorten the pressing time, pressing may be performed at a temperature equal to or higher than the glass transition temperature (Tg) of the binder resin 2 constituting the thermally conductive sheet precursor 7. The pressing time may be, for example, in the range of 10 seconds to 5 minutes, or may be in the range of 30 seconds to 3 minutes. For example, the pressure during pressing is preferably in the range of 0.2 to 0.7 MPa. In addition, the pressing temperature and pressing time are preferably in the range of room temperature to 90°C. If the thermal conductive sheet 1 is easily crushed, a low temperature (for example, about 25 to 40°C) and a short time (about 10 seconds) are preferable, and if the thermal conductive sheet 1 is not easily crushed, a high temperature (about 90°C) and a long time (about 3 minutes) are preferable.
[0063] In step D, instead of pressing the thermally conductive sheet precursor 7, the regular shape of the surface of the cushion 8 or the film 9 may be transferred to the surface of the thermally conductive sheet precursor 7 by the following method. For example, the thermally conductive sheet precursor 7 and the cushion 8 or the film 9 may be placed in a vacuum pack and tightly attached to each other, without using a press machine, to transfer the shape (pattern) of the surface of the cushion 8 or the film 9 to the surface of the thermally conductive sheet precursor 7. Alternatively, the thermally conductive sheet precursor 7 may be sandwiched between the cushion 8 or the film 9, and the shape (pattern) of the surface of the cushion 8 or the film 9 may be transferred to the surface of the thermally conductive sheet precursor 7 by the load of the thermally conductive sheet precursor 7 or the weight of the cushion 8 or the film 9, without using a special machine.
[0064] In this manner, in the step D, the thermal conductive sheet precursor 7 is pressed without physical processing such as polishing, so that the arithmetic mean roughness (Sa) of the surface is 5.0 μm or more and the roughness of the surface is 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 / W. Therefore, the thermally conductive sheet 1 obtained in step D is less likely to trap air during mounting, and the air can be easily released, while the difference in thermal resistance due to load can be reduced, as described above.
[0065] In addition, in this manufacturing method, the thermal conductive sheet 1 having a regular shape (unevenness) on the surface can be produced only by applying pressure from the outside, and there is no need to perform physical processing (such as physical scraping, processing, polishing, etc.) on the thermal conductive sheet precursor 7. This prevents the risk of powder falling off of the conductive material (e.g., fibrous filler 3) in the thermal conductive sheet 1, and avoids the risk of short circuiting when the thermal conductive sheet is mounted on an IC chip on which circuits are integrated. Therefore, the thermal conductive sheet 1 obtained by this manufacturing method has the advantage that there is no restriction on the places of use compared to a thermal conductive sheet that has been subjected to physical processing. Furthermore, in this manufacturing method, even if the thermal conductive sheet precursor 7 has an arbitrary thickness, the thermal conductive sheet 1 having a regular shape on the surface can be easily obtained.
[0066] Furthermore, in the case of transferring a regular shape to the surface of the thermal conductive sheet precursor 7 by pressing the thermal conductive sheet precursor 7 in step D, the regular shape (unevenness) formed in the thermal conductive sheet 1 can be made less likely to disappear by controlling the content of the binder resin 2 in the thermal conductive sheet precursor 7 (so that it is not too high) as described above.
[0067] <Electronic equipment> For example, the thermally conductive sheet 1 can be disposed between a heat generating body and a heat sink to form an electronic device (thermal device) having a structure in which the sheet is disposed between the heat generating body to dissipate heat generated by the heat generating body to the heat sink. The electronic device has at least the heat generating body, the heat sink, and the thermally conductive sheet 1, and may further have other members as necessary.
[0068] The electronic device according to the present technology has a surface arithmetic mean roughness (Sa) of 5.0 μm or more between the heat generating body and the heat sink, and a surface roughness of 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 The electronic device has a thermally conductive sheet 1 with a thermal conductivity of less than 1 / W. In an electronic device having such a configuration, the thermally conductive sheet 1 is less likely to contain air during mounting, and the thermal resistance difference due to load can be reduced, so that the thermally conductive sheet 1 can be prevented from folding when pressure is applied during mounting. Therefore, it is possible to suppress unevenness in the in-plane thickness of the thermally conductive sheet 1 and deterioration of the thermal resistance of the thermally conductive sheet 1 due to an increase in contact thermal resistance. In addition, when a large-sized thermally conductive sheet 1 is picked up by an automatic machine and mounted on an IC chip as a heating element, since the surface of the thermally conductive sheet 1 is not smooth, it is possible to prevent the thermally conductive sheet 1 from being mounted from multiple ends or the thermally conductive sheet 1 from being mounted parallel to the IC chip. Therefore, it is possible to prevent air from being contained in the center between the thermally conductive sheet 1 and the IC chip in the electronic device.
[0069] The heat generating body is not particularly limited, and examples thereof include electronic components that generate heat in an electric circuit, such as integrated circuit elements such as a CPU, a GPU (Graphics Processing Unit), a DRAM (Dynamic Random Access Memory), and a flash memory, as well as transistors, resistors, etc. Heat generating bodies also include components that receive optical signals, such as optical transceivers in communication devices.
[0070] The heat dissipator is not particularly limited, and examples thereof include heat sinks and heat spreaders that are used in combination with integrated circuit elements, transistors, optical transceiver housings, etc. Examples of materials for heat sinks and heat spreaders include copper and aluminum. In addition to heat spreaders and heat sinks, the heat dissipator may be anything that conducts heat generated from a heat source and dissipates it to the outside, and examples of the heat dissipator include radiators, coolers, die pads, printed circuit boards, cooling fans, Peltier elements, heat pipes, vapor chambers, metal covers, housings, etc. The heat pipe is, for example, a hollow structure that is cylindrical, approximately cylindrical, or flattened.
[0071] FIG. 3 is a cross-sectional view showing an example of a semiconductor device to which a thermally conductive sheet is applied. For example, as shown in FIG. 3, the thermally conductive sheet 1 is mounted on a semiconductor device 50 built into various electronic devices and sandwiched between a heat generating body and a heat dissipating body. The semiconductor device 50 shown in FIG. 3 includes an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. The thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the heat sink 53, and together with the heat spreader 52, constitutes a heat dissipating member that dissipates heat from the electronic component 51. The mounting location of the thermally conductive sheet 1 is not limited to between the heat spreader 52 and the electronic component 51, or between the heat spreader 52 and the heat sink 53, and can be appropriately selected according to the configuration of the electronic device or the semiconductor device. The heat spreader 52 is formed, for example, in a rectangular plate shape, and has a main surface 52a facing the electronic component 51 and a side wall 52b standing along the outer periphery of the main surface 52a. The heat spreader 52 has a thermally conductive sheet 1 provided on the main surface 52a surrounded by the side wall 52b, and a heat sink 53 provided, with the thermally conductive sheet 1 interposed between the main surface 52a and the other surface 52c opposite the main surface 52a. EXAMPLES
[0072] Hereinafter, examples of the present technology will be described, but the present technology is not limited to these examples.
[0073] <Example 1> In Example 1, as shown in Table 1, 24% by volume of alumina particles with an average particle size of 4 μm, which had been subjected to coupling treatment with a silane coupling agent, 24% by volume of aluminum nitride particles with an average particle size of 1.3 μm, and 24% by volume of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous filler were mixed into a two-part addition reaction type liquid silicone to prepare a silicone composition. 28% by volume of the two-part addition reaction type liquid silicone resin was mainly composed of organopolysiloxane. The obtained silicone composition was extrusion molded into a hollow rectangular prism-shaped mold (70 mm x 70 mm) to mold a silicone molded body of 70 mm square. The silicone molded body was heated in an oven at 100°C for 6 hours to obtain a silicone cured product. The silicone cured product was cut with a slicer to a thickness of 0.3 mm to obtain a thermal conductive sheet precursor. As shown in FIG. 2, a rubber cushion (surface arithmetic mean roughness (Sa)=29.915 μm) having a regular shape on the surface of a thermally conductive sheet precursor 7 sandwiched between release films 6 (PET films subjected to release treatment) was attached and pressed. The pressing conditions were 0.5 MPa, temperature 40° C., and time 10 sec. The thermally conductive sheet 1 after pressing was externally processed to a 60 mm×60 mm square.
[0074] <Example 2> In Example 2, a thermally conductive sheet precursor 7 was obtained in the same manner as in Example 1, and an embossed film (surface arithmetic mean roughness (Sa)=26.736) having a regular shape on its surface was attached to the surface of the thermally conductive sheet precursor 7 sandwiched between release films 6 (PET films subjected to release treatment) as shown in FIG. 2, and pressed. The pressing conditions were 0.5 MPa, temperature 40° C., and time 10 sec. The thermally conductive sheet 1 after pressing was externally processed to a 60 mm×60 mm square.
[0075] <Comparative Example 1> In Comparative Example 1, a thermally conductive sheet precursor 7 was obtained in the same manner as in Example 1, and a copy paper (A4 size) was attached to the surface of the thermally conductive sheet precursor 7 sandwiched between release films 6 (PET films subjected to release treatment), and then pressed. The pressing conditions were 0.5 MPa, temperature 40°C, and time 10 seconds. The thermally conductive sheet 1 after pressing was externally processed to a 60 mm x 60 mm square.
[0076] <Comparative Example 2> FIG. 4 is a cross-sectional view for explaining a method of pressing a pressed thermally conductive sheet precursor without attaching a film or cushion having a regular shape on the surface in Comparative Example 2. In Comparative Example 2, a thermally conductive sheet precursor 7 was obtained in the same manner as in Example 1, and as shown in FIG. 4, a rubber cushion having a regular shape on the surface or an embossed film having a regular shape on the surface of the thermally conductive sheet precursor 7 sandwiched between release films 6 (PET films subjected to release treatment) was not attached, and the thermally conductive sheet precursor was pressed as it is. The pressing conditions were 0.5 MPa, temperature 40° C., and time 10 sec. The thermally conductive sheet 1 after pressing was externally processed to a 60 mm×60 mm square.
[0077] <Comparative Example 3> In Comparative Example 3, a thermally conductive sheet precursor 7 was obtained in the same manner as in Example 1, and the thermally conductive sheet precursor 7 was externally processed to a 60 mm×60 mm square without being pressed.
[0078] <Comparative Example 4> In Comparative Example 4, a thermally conductive sheet precursor 7 was obtained in the same manner as in Example 1, and the surface of the thermally conductive sheet precursor 7 was polished using sandpaper (manufactured by Sankyo Rikagaku Co., Ltd., product name: FUJISTAR waterproof abrasive paper DCCS-1000 (#1000)). Specifically, an operation of dragging the abrasive paper with a 300 g weight on the thermally conductive sheet precursor 7 was performed 100 times. The thermally conductive sheet precursor 7 after polishing was externally processed to a 60 mm x 60 mm square.
[0079] <Comparative Example 5> In Comparative Example 5, as shown in Table 1, 44% by volume of alumina particles with an average particle size of 2 μm, which had been subjected to coupling treatment with a silane coupling agent, and 14% by volume of pitch-based carbon fibers with an average fiber length of 200 μm were mixed with a two-component addition reaction type liquid silicone to prepare a silicone composition, and 42% by volume of a material mainly composed of organopolysiloxane was used as the two-component addition reaction type liquid silicone resin. Except for this, a thermal conductive sheet precursor 7 was obtained in the same manner as in Example 1, and the thermal conductive sheet precursor 7 was pressed in the same manner as in Example 1. The pressing conditions were 0.5 MPa, temperature 40° C., and time 10 sec. The thermal conductive sheet 1 after pressing was externally processed to a 60 mm×60 mm square.
[0080] <Shore type OO hardness> The Shore type OO hardness of the thermal conductive sheets 1 obtained in Examples 1 and 2 and Comparative Examples 1, 2, and 5 and the thermal conductive sheet precursor 7 obtained in Comparative Examples 3 and 4 was determined by a measurement method conforming to ASTM-D2240, in which five 2 mm thick thermal conductive sheets 1 (or thermal conductive sheet precursor 7) were stacked to a thickness of 10 mm, and measurements were taken at five points on one side and ten points on both sides in total. The results are shown in Table 1.
[0081] <Tackiness> The tackiness of the thermal conductive sheets 1 immediately after production in Examples 1 and 2 and Comparative Examples 1, 2, and 5, and the thermal conductive sheet precursor 7 immediately after production in Comparative Examples 3 and 4, was evaluated by visual inspection. Specifically, when there was no tackiness, it was evaluated as "x" (OK), and when there was tackiness, it was evaluated as "o" (NG). The results are shown in Table 1.
[0082] <Unevenness 10 minutes after processing> Ten minutes after producing the thermally conductive sheets 1 obtained in Examples 1 and 2 and Comparative Examples 1, 2, and 5, and the thermally conductive sheet precursor 7 obtained in Comparative Examples 3 and 4, the surface irregularities of the thermally conductive sheets 1 (or the thermally conductive sheet precursor 7) were visually evaluated. When the irregularities on the sheet surface could be visually confirmed, the sheet was evaluated as "◯" (OK), and when the irregularities on the sheet surface could not be visually confirmed, the sheet was evaluated as "×" (NG). The results are shown in Table 1.
[0083] <Unevenness one week after processing> One week after the thermal conductive sheets 1 obtained in Examples 1 and 2 and Comparative Examples 1, 2, and 5 and the thermal conductive sheet precursor 7 obtained in Comparative Examples 3 and 4 were produced, the surface irregularities of the thermal conductive sheets 1 (or the thermal conductive sheet precursor 7) were visually evaluated. When the irregularities on the sheet surface could be visually confirmed, the sheet was evaluated as "◯" (OK), and when the irregularities on the sheet surface could not be visually confirmed, the sheet was evaluated as "×" (NG). The results are shown in Table 1.
[0084] <Sheet height from copper plate (maximum)> 5 is a perspective view for explaining an example of a method for measuring the height of the thermally conductive sheet from the copper plate. As shown in FIG. 5, the thermally conductive sheet 1 (60 mm×60 mm, thickness 0.3 mm) obtained in Examples 1 and 2 and Comparative Examples 1, 2, and 5, or the thermally conductive sheet precursor 7 (60 mm×60 mm, thickness 0.3 mm) obtained in Comparative Examples 3 and 4 was lifted with an adsorption pad 20 and set on a 10 cm square copper plate 21 (JIS H 3100 C1100P). After removing the thermally conductive sheet 1 (or the thermally conductive sheet precursor 7) from the adsorption pad 20, the height from the surface of the copper plate 21 to the upper surface of the thermally conductive sheet 1 (or the thermally conductive sheet precursor 7) was measured with a non-contact measuring device (product name: KEYENCE ONE-SHOT 3D VR-5000). The results are shown in Table 1.
[0085] <Air bubbles on the copper plate> Based on the result of the height of the thermally conductive sheet 1 from the copper plate 21, the presence or absence of air bubbles in the thermally conductive sheet 1 (or the thermally conductive sheet precursor 7) on the copper plate 21, that is, whether the thermally conductive sheet 1 (or the thermally conductive sheet precursor 7) was degassed, was evaluated. The results are shown in Table 1.
[0086] <Arithmetic mean roughness (Sa)> At the same time as measuring the height of the thermal conductive sheet 1 (or the thermal conductive sheet precursor 7), the arithmetic mean roughness (Sa) [μm] of the thermal conductive sheet 1 (or the thermal conductive sheet precursor 7) was measured. The calculated area for the arithmetic mean roughness (Sa) was 24.193 cm × 18.16 cm. The results are shown in Table 1.
[0087] <Thermal resistance, thermal resistance difference> Prepare a thermally conductive sheet 1 (or thermally conductive sheet precursor 7) with a diameter of 20 mm and a thickness of 0.3 mm. The thermal resistance (℃ cm 2 / W) was measured according to a method in accordance with ASTM-D5470. 2 Thermal resistance (℃ cm) of the thermal conductive sheet 1 (or the thermal conductive sheet precursor 7) when a pressure of 2 / W) and 5kgf / cm 2 Thermal resistance (℃ cm) of the thermal conductive sheet 1 (or the thermal conductive sheet precursor 7) when a pressure of 2 The difference from the measured value was calculated and the results are shown in Table 1.
[0088] [Table 1]
[0089] In Examples 1 and 2, the arithmetic mean roughness (Sa) of the surface is 5.0 μm or more, and the surface roughness is 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 It was found that a thermally conductive sheet with a thermal conductivity of less than 1 / W could be obtained.
[0090] On the other hand, in Comparative Examples 1 to 5, the arithmetic mean roughness (Sa) of the surface was 5.0 μm or more, and the surface roughness was 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5kgf / cm at a thickness of 0.3mm 2 The difference in thermal resistance between 2 It was found that a thermally conductive sheet having a thermal conductivity of less than 1 / W could not be obtained.
[0091] Furthermore, from the results of Examples 1 and 2 and Comparative Examples 1 to 4, it was found that even if the composition of the thermally conductive sheets was the same, there was a difference in the thermal resistance.
[0092] The thermally conductive sheets (or thermally conductive sheet precursors) obtained in Comparative Examples 1 to 3 were subjected to a low load (1 kgf / cm2 ) area, and high load (5kgf / cm 2 It is considered that the contact was improved when the load was applied, and therefore the difference in thermal resistance due to the load became larger compared to the thermal conductive sheets obtained in Examples 1 and 2.
[0093] The thermal conductive sheet precursor obtained in Comparative Example 4 had a thermal resistance difference of 0.10°C cm when measured under varying loads, similar to the thermal conductive sheets obtained in Examples 1 and 2. 2 / W. In Comparative Example 4, the surface was polished with sandpaper, which improved the smoothness of the surface, and although the surface irregularities were small, it is believed that the contact thermal resistance was reduced, thereby reducing the thermal resistance difference due to the load. However, in Comparative Example 4, the surface of the thermal conductive sheet precursor was polished with sandpaper, that is, the thermal conductive sheet precursor was physically processed, so that some of the carbon fibers fell off or broke, and the thermal conductive sheet precursor was found to have a blackened appearance.
[0094] In addition, the arithmetic mean roughness (Sa) of the surface of the thermally conductive sheet (or thermally conductive sheet precursor) obtained in the examples and comparative examples was measured. As a result, it was found that when the thermally conductive sheet precursor was pressed using a flat A4 paper as in Comparative Example 1 or a metal plate as in Comparative Example 2, the smoothness of the surface of the thermally conductive sheet was higher, that is, the arithmetic mean roughness (Sa) of the surface of the thermally conductive sheet was smaller, compared to when the thermally conductive sheet precursor was pressed using a film or cushion having a regular shape (unevenness) on the surface as in Examples 1 and 2. In addition, although the thermally conductive sheet obtained in Comparative Example 3 had a surface arithmetic mean roughness (Sa) of 5.0 μm or more, no regularity was confirmed in the surface shape, and the entire surface was found to be rough.
[0095] Furthermore, in Examples 1 and 2, it was found that by attaching a film or cushion having a regular shape (unevenness) on the surface to the thermal conductive sheet precursor and pressing it, the unevenness is transferred to the surface of the thermal conductive sheet after processing (unevenness remains).
[0096] On the other hand, in Comparative Example 5, as in Examples 1 and 2, a film or cushion having a regular shape (unevenness) on the surface was attached to the thermal conductive sheet precursor and pressed, but it was found that the unevenness was not transferred (no unevenness remained) to the surface of the thermal conductive sheet after processing. The thermal conductive sheet obtained in Comparative Example 5 had a high silicone resin content of 42 volume %, which is thought to have made it difficult for the unevenness to be transferred to the surface. This is also supported by the fact that the arithmetic mean roughness (Sa) of the surface of the thermal conductive sheet obtained in Comparative Example 5 was less than 5.0 μm.
[0097] In addition, the height of the thermally conductive sheet from the copper plate was measured, and it was found that the thermally conductive sheets obtained in Examples 1 and 2 followed the copper plate. The thermally conductive sheets obtained in Examples 1 and 2 had an arithmetic mean roughness (Sa) of 5.0 μm or more on the surface, that is, the surface was uneven, which is thought to have reduced tackiness. On the other hand, the thermally conductive sheets obtained in Comparative Examples 1 and 2 had a smooth surface and tackiness compared to the thermally conductive sheets obtained in Examples 1 and 2, and air bubbles and floating on the copper plate were observed. The thermally conductive sheets obtained in Comparative Examples 1 and 2 had more tack compared to the thermally conductive sheets obtained in Examples 1 and 2, and it is thought that when the thermally conductive sheets were separated from the suction pad, the thermally conductive sheets at the parts in contact with the suction pad did not adhere sufficiently to the copper plate, causing air bubbles to be included.
[0098] In the past, in order to improve the contact of a thermal conductive sheet (thermal resistance of the thermal conductive sheet), many studies have been conducted on the technology of how to make the thermal conductive sheet smooth. However, the results of the examples and comparative examples show that the smoothness of the thermal conductive sheet is not the only important factor, and that even if the surface of the thermal conductive sheet has some unevenness, the difference in thermal resistance due to load can be reduced.
[0099] It is also possible to reduce the difference in thermal resistance due to the load of the thermal conductive sheet by physically processing the surface of the thermal conductive sheet as in Comparative Example 4, but in this case, the locations where the thermal conductive sheet can be used are limited due to the risk of short circuiting as described above. On the other hand, it was suggested that the thermal conductive sheet in Examples 1 and 2, in which unevenness (regular shape) is transferred to the surface by pressing, does not require physical processing of the surface as in Comparative Example 4, and therefore can reduce the risk of short circuiting compared to the thermal conductive sheet in Comparative Example 4. [Explanation of symbols]
[0100] 1 Thermally conductive sheet, 2 Binder resin, 3 Fibrous filler, 4 Other thermally conductive materials, 5 Pressing device, 6 Release film, 7 Thermally conductive sheet precursor, 8 Cushion having a regular shape on its surface, 9 Film having a regular shape on its surface, 10 Laminate, 11 Laminate, 20 Suction pad, 21 Copper plate, 50 Semiconductor device, 51 Electronic component, 52 Heat spreader, 52a Main surface, 52b Side wall, 52c Other surface, 53 Heat sink
Claims
1. The arithmetic mean roughness (Sa) of the surface of the thermal conductive sheet is 5.0 μm or more, 1 kgf / cm at a thickness of 0.3 mm 2 and thermal resistance of 5 kgf / cm at a thickness of 0.3 mm 2 The difference in thermal resistance between 2 / W or less.
2. The thermally conductive sheet according to claim 1 , wherein the surface has a regular shape.
3. The thermal conductive sheet according to claim 1 or 2, comprising a fibrous filler, the fibrous filler being oriented in the thickness direction.
4. The thermal conductive sheet according to any one of claims 1 to 3, comprising a silicone resin as a binder resin.
5. The thermally conductive sheet according to claim 4 , wherein the silicone resin content is less than 42% by volume.
6. The thermally conductive sheet according to any one of claims 1 to 5, further comprising another thermally conductive material other than the fibrous filler.
7. The thermally conductive sheet according to claim 6 , wherein the other thermally conductive material is at least one of alumina and aluminum nitride.
8. A step A of preparing a thermally conductive composition including a binder resin and a fibrous filler; A step B of forming a molded block from the thermally conductive composition; A step C of slicing the molded block into sheets to obtain a thermal conductive sheet precursor; and a step D of pressing the thermally conductive sheet precursor to obtain a thermally conductive sheet, The thermal conductive sheet has a surface arithmetic mean roughness (Sa) of 5.0 μm or more, The thermal conductive sheet has a resistance of 1 kgf / cm at a thickness of 0.3 mm. 2 and thermal resistance of 5 kgf / cm at a thickness of 0.3 mm 2 The difference in thermal resistance between 2 / W or less.
9. The method for producing a thermal conductive sheet according to claim 8 , wherein in the step D, the thermal conductive sheet precursor is pressed to transfer a regular shape to a surface of the thermal conductive sheet precursor.
10. 10. The method for producing a thermal conductive sheet according to claim 8 or 9, wherein in the step D, a film or cushion having a regular shape on its surface is attached to the surface of the thermal conductive sheet precursor and pressed, thereby transferring the shape of the film or cushion surface to the surface of the thermal conductive sheet precursor.
11. The method for producing a thermal conductive sheet according to any one of claims 8 to 10, wherein a surface of the thermal conductive sheet is a pressed surface.
12. A heating element; A heat sink; An electronic device comprising the thermally conductive sheet according to any one of claims 1 to 7, disposed between the heat generating body and the heat dissipating body.
Citation Information
Patent Citations
Ultrasonic probe
JP1982052299A
Preparation of monascus pigment having strong yellow color
JP1986078389A
Thermally conductive sheet and method of producing the same
JP2012023335A
Thermally conductive compact and manufacturing method thereof
JP2014027144A
Thermally conductive sheet
JP2015035580A
